(untitled) (Estudos em Design, 2021)
Editores Cristina Portugal Rita Maria de Souza Couto Avaliadores desta edição v. 29, n. 1 (2021) Adriana Gralow Alexandre Farbiarz Alexandre Santos de Oliveira Aline Eyng Savi Álvaro José Barbosa Sousa Ana Veronica Pazmino André Ribeiro de Oliveira Angélica Adverse Antônio Ferreira Colchete Filho Beany Monteiro Cássia Letícia Carrara Carlo Franzato Clice Mazzilli Claudio Silva Cristina Portugal Cyntia Santos Malaguti Daniel Raposo Daniela Alves Danielly Amatte Lopes Doris Kosminsky Edson Rufino de Souza Eloiza Andrade Corrêa Everton da Silva Fernanda Cardoso Fernanda Henriques Fernando Fogliano Frederico Braida Gabriel Patrocínio Guilherme Englert Corrêa Meyer Hugo Sant’Anna Ione Maria Ghislene Bentz Joao Eduardo chagas Sobral Joana Quental Kando Fukushima Kátia Carvalhaes Pêgo Leticia Affini Letícia Pedruzzi Fonseca Luciane Fadel Luiz Agner Luiza Falcão Soares Cunha Luiza Novaes Márcio Guimarães Marcos Braga Maria Cristina Ibarra Maria José Jorente Mariana Cantisani Padu Mariano Lopes de Andrade Neto Maristela Mitsuko Ono Monica Tavares Otniel Josafat López Altamirano Paula Piva Linke Rafael Efrem Rafaella Peres Raimundo Lopes Diniz Ranielder Fábio de Freitas Raquel Noronha Ravi Passos Ricardo Cunha Lima Rogério José Câmara Romero Tori Rosimeri Franck Pichler Sandra Souza Sérgio Luciano da Silva Tiago Barros Pontes Silva Vera Damazio Virginia Tiradentes Souto Viviane Nunes Wagner Bandeira Walter Correia